PERANCANGAN PROMOSI EVENT SURFING USIA GROMMET DI PASIR PUTIH PADANG MELALUI MEDIA POSTER - Budi Rilvantino, Dra. Zubaidah A, M.Sn, Drs. Erwin A, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
The purpose of this design is to create a promotion event surf for media design surf as means of communication in inform target audience that will support the implementation of this surfing events is reached design. While the design process used was descriptive procedural models through data collection processes, observation, interviews, further documentation is analyzed using the theory of SWOT analysis. The drafting process will be published in the form of media poster. By using more varied media campaign, then the goal is reached to capture people interest especially children to advance tourism in Pasir Putih beach peak Batu Muaro Padang city.